Dissipation of Hydraulic Energy in Stilling Basin by Cutting Baffle Blocks - Raad H. Irzooki; Abd-Alsabir I. Bakir; Idan I. Kadhban (Tikrit Journal of Engineering Sciences, 2005)
This study was undertaken to evaluate the hydraulic performance of stilling basin with unusual shapes of baffle blocks. Seven groups of baffle blocks were selected for this purpose , these blocks were cut within a different forms, three of these groups were cut with angle (15o, 30o, 45o) horizontally. Another three groups were cut with the same above angles, but vertically. The seventh group was cut with semi-cylindrical section (shown from side view). For a comparison, standard trapezoidal baffle blocks were used. Dimensional analysis technique was used to obtain the dimensionless parameters of hydraulic performance of the cutting baffle blocks and the drag force applied on these blocks. Laboratory experiments were carried out on one raw of the cutting baffle blocks for each model. The results indicated that the cutting baffle blocks are generally better than the standard blocks in dissipation of a hydraulic energy and reduction of a hydraulic jump length, but a ratio of drag force applied on cutting baffle blocks was greater than this ratio on the standard blocks. For the same flow conditions and angle of cut, the baffle blocks of vertically cutting gave a better results for energy dissipation and reduction in the length of the hydraulic jump than the baffle blocks of horizontally cutting, but the drag force applied on the baffle blocks with a vertically cutting was greater than applied on a blocks with horizontally cutting. Also, the results indicated that an agreement in the hydraulic performance between the baffle blocks which were cut at (45o) vertically and the baffle blocks of semi-cylindrical cutting. The cutting baffle blocks gives a greater value of the energy dissipation which was (80.62%) than the standard blocks and greater value of reduction in the hydraulic jump length which was(37.5%),also these blocks gives maximum increase of the drag force ratio which was (97%) greater than its value on the standard baffle blocks.